Avaliação da política pública de assistência estudantil: a realidade do programa de auxílio moradia na UFC – campi de Fortaleza - Ribeiro, Claryssa Lourenço (2023)
This research aims to evaluate the implementation of the student assistance policy, focusing on housing assistance, at the Federal University of Ceará (UFC). The aim is, therefore, to observe its relationship with other policies, of a social and educational nature, in order to understand its indispensability as a guaranteeing instrument for the expansion of educational policy. It is necessary to reflect that it is not enough to create more vacancies to increase accessibility in federal public universities, if there is no policy to guarantee that those students in vulnerable situations will be able to effectively attend and complete the chosen graduations, in order to concretely reduce social inequalities. To achieve the objective of this study, based on the assumptions of in-depth evaluation (RODRIGUES, 2008), an analysis of the conceptual bases of the National Student Assistance Program (PNAES) is carried out, as well as an explanation of the context of formulation of the policy, analyzing the historical, political and economic moment that culminated in the blossoming of the student assistance policy. In addition, through a semi-structured interview, the perception of the former manager of the Pro-Rectory of Student Affairs (PRAE) on student assistance at the university is analyzed, especially during the period of the COVID-19 pandemic. To complement the evaluation, the opinion of 71 students benefiting from housing assistance is also evaluated, using an electronic form. As a result, it is observed that the expansion of the masses verified in PT governments was curbed with the advent, increasingly present, of neoliberal ideals, whose focus on budget control goes against the increase and/or maintenance of social programs. With that, the challenge faced in the current political scenario is the maintenance (and not retrogression) of welfare measures, which effect the democratization of higher education, reducing evasion and inequalities. In addition, it appears that the perception of the former Dean is that there was no significant budget reduction in student assistance at the university, in addition to that, in the pandemic period, UFC established new aid and promoted the modernization of communication and procedures administrative offices of the PRAE. Through the form for students, it is identified that a large part considered not enrolling in the course because of difficulty in staying at the university, as well as, most have already been beneficiaries of some other student assistance action of the university or enjoyed services, such as the University Restaurant. It should be noted that the resource passed on through the housing allowance is essential for the cost of rent and other expenses related to housing. It is concluded that UFC student assistance, including housing assistance, contributes to the permanence and completion of students, in addition to allowing their access to complementary activities available at the University